Protection of children’s privacy on electronic media - Thamangraksat, Sukwasa (KASEM BUNDIT JOURNAL, 2019)
The main purpose of this thesis was to study the problems of violation of children’s privacy. Legal measures involved with the child protection and personal data protection , particularly the child protection Act BE. 2546 was compared with foreign laws on Privacy Protection. It was revealed that, there was no central law protecting personal data officially. At the time when this research was being done, a law known as “the draft of Personal Data Protection Act” was in preparation. However, this draft did not specifically protect personal data of children because it was not required to obtain parental consent before collecting, using or disclosing personal data of children. Although the Child Protection Act 2003 mentions the protection of some children’s data, but it did not cover the use of personal data.